DIWANU LUGATI’T-TURK AND CONTEMPORARY LINGUISTICS - TİMUR KOCAOĞLU (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
The branches of linguistics such as Sociolinguistics and Applied Linguistics are relatively young disciplines compared to the much older fields of linguistics such as General Linguistics, Historical Linguistics, and Theoretical Linguistics. 1 These new disciplines have not only brought new dimensions to linguistics, but have also expanded our general understanding of the world languages. In this article, I will attempt to evaluate both the approaches and techniques that had been employed in the composition of the eleventh century Turkic dictionary Diwanu Lugati’t-Turk (DLT) by Mahmud Kashghari (1072-1077).2 To undertake this task, I will examine this work consistent with the most recent approaches in Applied Linguistics and Sociolinguistics.